The type of ethnomathematics in fish trading in sapuran market, Wonosobo - Awal Mulia Rachmanto; Riawan Yudi Purwoko (Universitas negeri Yogyakarta, 2020)
This study aims to reveal the type of ethnomathematics used in the process of counting fish in Sapuran Market, Wonosobo, which can be applied in teaching processes. The method used in this study is the observation of fish trading and interviews with fish traders in Sapuran Market, Wonosobo. The research findings show that the process of counting fish in the market applies ethnomathematics, including the addition of integer and reduction of the integer. The mathematical concept used in the addition operation is the storing technique, while the reduction operation applies the borrowing technique. The implementation of mathematics teaching using the ethnomathematics approach adopted from the activities of fish counting at Sapuran Market, Wonosobo can help improve students’ understanding of the addition and reduction materials for elementary school.